Intercultural Cities Policy and Practice for a New Era (Global Diversities,, 2018)
This book sets out to explore the political and social potential of intercultural policy for cities by bringing together advances in the areas of urban planning and intercultural theory. In recent years, demographic changes in cities in many parts of the world have led to increasing concerns about inter-ethnic tensions, social inequality, and racial discrimination. By virtue of their intermediate status-neither national nor regional, at the same time global and local-cities are in a particularly good position to formulate policy frameworks that will contribute to the well-being of all citizens, regardless of their origins. Certain cities have made significant advances in this domain, but until now very little work has been done to understand the underlying principles and processes behind the creation of intercultural policies and programs. The overall goal of this volume is to facilitate conversations between researchers and practitioners in their efforts to make cities more inclusive by leveraging recent advances in the field of intercultural policy and practice, but it is also intended to generate knowledge about the conditions, obstacles and strategies that make intercultural cities part of a common future. This interdisciplinary collection will be of great interest to scholars and policy makers including in areas of urban studies, public policy, anthropology, sociology, globalization and the wider social sciences.